Response to therapeutic monoclonal antibodies for multiple myeloma in African Americans versus whites. Issue 22 (10th October 2018) - Chehab, Sarah; Zhang, Chao; Panjic, Elyse H.; Chen, Zhengjia; Kaufman, Jonathan L.; Lonial, Sagar; Nooka, Ajay; Harvey, R. Donald
Abstract : Background: Myeloma occurs disproportionately in African Americans, with disparities in outcomes potentially caused by access to care, cytogenetics, and immunity. A gap in knowledge of immune function dissimilarities between African Americans and whites exists. Data for other diseases suggest innate differences in immunity and inflammatory markers, with potential implications for therapeutic monoclonal antibodies reliant on secondary immune activation for activity. Methods: Patients receiving daratumumab or elotuzumab, lenalidomide, and dexamethasone were retrospectively studied with a primary endpoint of response at 2 (daratumumab) or 4 months (elotuzumab). Secondary endpoints included stable disease or better at the same points, treatment duration, time to best response, and adverse events. Results: Eighty patients were included; baseline characteristics were balanced with the exception of the stage at diagnosis, which was more advanced in African Americans. No statistically significant difference in response was seen: 37.9% in whites versus 11.8% in African Americans with daratumumab ( P = .090) and 60% in whites versus 44% in African Americans with elotuzumab ( P = .462). There were no differences in the duration of treatment, the time to best response, or adverse events. Common potential immune‐related adverse events in both arms were fatigue (39%), back pain (30%), and infusion reactions (40%). Anemia was significantly associated with a response to daratumumab ( P = .02); no patients without anemia responded at 2 months, whereas 34.4% of patients with anemia did. Conclusions: No significant difference in response, duration of treatment, or time to response was seen by race, although a trend toward greater early response rates in whites was observed. In these cohorts, as in other analyses, African American patients tended to present with later stage disease. Abstract : African American patients with myeloma do not appear to have different responses to monoclonal antibodies than whites. The presence of anemia may predict the response to daratumumab.